ANALYSIS OF ENERGY CONCEPTS THROUGH PHET SIMULATION: A CASE STUDY ON SKATE PARK - Sudirman, Sudirman; Marwoto, Putut; Nugroho, Sunyoto Eko (EduFisika: Jurnal Pendidikan Fisika, 2024)
This study aims to analyze students' understanding of energy concepts through the PhET simulation in the case of the Skate Park. Energy concepts, including kinetic energy, potential energy, and mechanical energy, often present challenges in physics education, particularly in the context of visual and interactive comprehension. In this study, the PhET "Energy Skate Park" simulation was used to observe energy changes in objects moving along a skate park track at various heights. The study involved high school students conducting experiments using this simulation to understand the basic principles of physics related to energy changes. Data were collected through direct observations and pre-test and post-test quizzes to assess the improvement in students' understanding of energy concepts. The results showed that using the PhET simulation significantly helped students understand the changes between kinetic energy, potential energy, and mechanical energy in a more tangible and visual context. The average post-test score (86.67) demonstrated an increase of 24 points compared to the pre-test score (62.67), with the standard deviation decreasing from 7.91 to 6.05, indicating a more consistent understanding among students. The simulation effectively assisted students in building conceptual schemas through interactive visualization and virtual experiments, aligning with constructivist theory, experiential learning, and multimedia learning theories.The simulation also demonstrated its potential to enhance student engagement and their ability to apply physics concepts to real-life situations.